2012
DOI: 10.9734/bjecc/2012/1291
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EDTA on Heavy Metals Phytoextraction by Jatropha gossypifolia Grown on Soil Collected from Dumpsites in Ekiti State Nigeria

Abstract: Jatropha gossypifolia has been known to thrive well in tropical climate, most importantly in Nigeria where they are found to grow naturally on dumpsites. The potential use of this robust tropical plant in phytoremediation technology should be advocated especially for developing countries. This study investigates the effect of enhanced phytoextraction on the accumulation of the following heavy metals; (Cd, Cr, Fe, Mn, Pb, Zn, Ni, Cu, Co and Sn) by J. gossypifolia cultivated on soil collected from dumpsites in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
4
8
1
Order By: Relevance
“…More copper was also found to be accumulated in the root than shoot by Luhach and Chaudhry, [11] and Ahmadpour et al [8] but to a lesser extent. This same trend was observed in J. gossypifolia and J. multifida, however, the concentration of copper accumulated in the root of J. gossypifolia in this study is lower than that reported by Awokunmi et al [12] for copper translocated to the root of J. gossypifolia in heavy metal contaminated soil from different dumpsites. Also, the accumulation of copper both in the root and shoot progresses as J. curcas had the highest followed by J. multifida, then J. gossypifolia having the least.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…More copper was also found to be accumulated in the root than shoot by Luhach and Chaudhry, [11] and Ahmadpour et al [8] but to a lesser extent. This same trend was observed in J. gossypifolia and J. multifida, however, the concentration of copper accumulated in the root of J. gossypifolia in this study is lower than that reported by Awokunmi et al [12] for copper translocated to the root of J. gossypifolia in heavy metal contaminated soil from different dumpsites. Also, the accumulation of copper both in the root and shoot progresses as J. curcas had the highest followed by J. multifida, then J. gossypifolia having the least.…”
Section: Discussionsupporting
confidence: 88%
“…Some of these studies clearly demonstrated the potential of J. curcas to phytoremediate heavy metals contaminated media. For the other species, the effect of EDTA on the phytoextraction of heavy metals by J. gossypifolia from dumpsite was reported by Awokunmi et al [12]. The success of J. curcas is attributed to its highly effective and dedicated mechanism against abiotic pressures making it possible to endure severe climatic condition including excessive dryness, arid and seriously polluted soils [13,14].…”
Section: Introductionmentioning
confidence: 91%
“…The composition of waste dumps varies widely with many human activities located close to dumpsites (Awokunmi et al, 2012). The general belief that wastes are sometimes hazardous to health cannot be over emphaized.…”
Section: Introductionmentioning
confidence: 99%
“…India has the potential of becoming the world's leading producer of biodiesel, as it can be "harvested," and produced from nonedible oils like Jatropha curcas, Pongamia pinnata, Madhuca indica plants etc (Awwokunmi et al 2012;Bauddh and Singh 2012a, b).…”
Section: Non-edible Oil Plants For Biofuels On Contaminated Soilmentioning
confidence: 99%